PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA TELKOM INDONESIA WIFI CORNER KOTABARU YOGYAKARTA - Septian Dwi Ryan Purnama; Jajuk Herawati; Ignatius Soni Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2019)
The aim of study is to find empirical proof for significant positive influence perception of price against customer loyalty through the customer satisfaction as an intervening variable Corner on Wifi new city of Yogyakarta and the positive significant influence quality of products against customer loyalty through the customer satisfaction as an intervening variable Corner on Wifi new city of Yogyakarta.Type of this research is quantitative research, the population in this study was 100 people customers wifi corner kotabaru. Samples used are as much as 100 people customers wifi corner kotabaru Yogyakarta motode retrieval the sample uses the accidental sampling with the formula arikunto. Data collection using the questionnaire. The method of analysis used multiple regression is supported by T-test.The results of the analysis show that significant positive effect price Perception towards customer satisfaction matters, product quality significantly positive effect against this thing, customer satisfaction, influence perception rates against customer loyalty is not a positive effect significantly to customer loyalty, The positive effect of product quality significantly to customer loyalty, the positive effect significantly to customer loyalty, perception of price has no effect significant positive toward customer loyalty through the customer satisfaction as an intervening variable, positive significant effect the quality of products against customer loyalty through customer satisfaction as an intervening variable.Key words : Price Perception, Quality Product, customer satisfaction and customer loyalty